A twentieth- and twenty-first-century piano étude soundworld: obsessions and self-portraiture in Philip Glass's Twenty Piano Études - Carroll, Máire (Royal Irish Academy of Music, 2023)
Philip Glass’s Twenty Piano Études are a monumental contemporary contribution to the piano étude genre with notable composers throughout history using the oeuvre as a means of creating their own distinctive pianistic vocabulary. While there is much literature available on Glass’s operatic and chamber works, little scholarly attention has been given to his solo piano music. His set of piano études was published in 2014 and literature on these piano studies is scant. The premise of the thesis positions piano étude writing at the fore of a composer’s creative output. Given the extensive period of time dedicated to étude collections, often composed over a decade or more, this thesis explores the capability of an étude and presents it as a burgeoning genre indicative of a composer’s collective soundworld. In order to investigate Glass’s Twenty Piano Études, the studies are placed within the context of the wider twentieth- and twenty-first-century piano étude genre. Through consideration of an étude’s deep level of purpose, one which examines studies as an embodiment of obsessive practice, emerging trends between an array of composers appear. Rhythmic, harmonic and intervallic virtuosic obsessions are presented using examples by composers and composer-pianists including Unsuk Chin, Marc-André Hamelin, Nikolai Kapustin, György Ligeti, Hélène de Montgeroult, Terry Riley and Igor Stravinsky. Glass’s association with the early minimalist movement is the subject of much academic discussion, therefore the significance of Glass’s études is inspected from both minimalist and non-minimalist perspectives. A complete performance of all twenty études in 2022 at the National Concert Hall, Dublin, and a recording of the collection in 2023 offers a unique performer’s interpretation and an audio track listing is presented alongside the thesis. The research sheds new light on how Glass’s Twenty Piano Études and the wider contemporary piano étude can be interpreted from scholarly and performance perspectives. The études are presented as key to understanding the scope of a composer’s soundworld, ultimately unveiling an intimate self-portrait of its composer.
Keywords: Music; Piano music; Piano étude; Philip Glass; Glass, Philip; Piano music - 20th century; Piano music - 21st century